COMPARATIVE ANTIBACTERIAL EFFICACY OF AGRICULTURAL WASTE-DERIVED PHYTOCHEMICAL EXTRACTS FROM Musa paradisiaca, Manihot esculenta Peels, and Acacia nilotica SEEDS AGAINST MULTIDRUG-RESISTANT ENVIRONMENTAL BACTERIAL ISOLATES - Adeyemi, Oluwasanmi Anuoluwapo; Oladejo, Faith Alexander; Talabi, Olaoluwa Temitope; Ogah, Jeremiah Ikhevha; Samson, Oyindamola John (FUDMA Journal of Sciences, 2026)
Antimicrobial resistance poses a severe global health threat, with projections indicating 39 million deaths between 2025 and 2050. Wastewater systems are major reservoirs for resistant bacteria and resistance genes, promoting their spread. Agricultural waste offers a promising, sustainable source for developing antimicrobial agents. This study examined the antibacterial activity of ethanolic and methanolic extracts from Musa paradisiaca (banana) peel, Manihot esculenta (cassava) peel, and Acacia nilotica seeds against bacterial isolates from industrial and domestic wastewater in Oyo State, Nigeria. Fifty-six bacterial isolates were obtained using standard microbiological methods. Plant materials underwent cold maceration extraction with ethanol and methanol (1:4 w/v) for 48 hours. Antibacterial effectiveness was evaluated through agar well diffusion assay, minimum inhibitory concentration testing, and antibiotic susceptibility profiling following CLSI M100-34 guidelines. Recovered isolates included Bacillus spp. (42.9%), Pseudomonas spp. (28.6%), Proteus spp. (14.3%), Enterobacter spp. (10.7%), and Salmonella spp. (3.6%). Methanolic M. paradisiaca extract showed superior antibacterial activity with mean inhibition zones of 18.6 ± 2.8 to 22.4 ± 3.2 mm, compared to M. esculenta (16.2 ± 2.0 to 18.2 ± 2.4 mm) and A. nilotica (14.2 ± 1.8 to 16.4 ± 2.1 mm). The lowest MIC value (0.0625 g/mL) was achieved with methanolic M. paradisiaca extract. Strong positive correlations between extract activity and quinolone susceptibility (r = 0.78-0.82, p < 0.01) suggest DNA gyrase-targeting mechanisms. These findings demonstrate that agricultural waste-derived phytochemicals, especially methanolic banana peel extract, possess substantial antibacterial potential against multidrug-resistant environmental bacteria, supporting agricultural waste valorisation for sustainable antimicrobial development and wastewater treatment.
Keywords: Multidrug-Resistant Bacteria; Waste Water